Semiquantification Study of [11C]-(R)-PK11195 PET Brain Images in Multiple Sclerosis - Narciso, Lucas Diovani Lopes; Schuck, Phelipi Nunes; Dartora, Caroline Machado; Matushita, Cristina Sebastião; Becker, Jefferson; Marques da Silva, Ana Maria (Revista Brasileira de Física Médica, 2016)
PET brain images with [11C]-(R)-PK11195 are being widely used to visualize microglial activation in vivo in neurodegenerative diseases, such as multiple sclerosis (MS). The aim of this study is to investigate the uptake behavior in juxtacortical and periventricular regions of [11C]-(R)-PK11195 PET brain images reformatted in different time intervals by applying three methods, seeking method and time interval that significantly differentiate MS patients from healthy controls. Semiquantitative SUV and SUVR methods were applied to PET images from different time intervals acquired from 10 patients with MS and 5 healthy controls. The results show significant difference between groups for SUV (p = 0.01) in 40 to 60 min interval, and SUVR with white matter as reference (p < 0.01) in 10 to 60 min interval, measured in the juxtacortical and periventricular regions.